CAREER DEVELOPMENT OF LECTURERS IN HIGHER EDUCATION: A CASE STUDY AT UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, INDONESIA - Seno Santoso, (Journal of Innovation Research and Knowledge, 2025)
Purpose: This study aims to analyze the strategies, supporting factors, and challenges in developing the careers of lecturers at Universitas Islam Syekh-Yusuf (UNIS) Tangerang, focusing on four key areas: academic qualification enhancement, scientific publications, professional development, and welfare incentives. Design/Methodology/Approach: A qualitative case study approach was used. Data were collected through in-depth interviews with university leaders, deans, and lecturers, as well as observation and document analysis. Data were analyzed using the Miles and Huberman interactive model. Findings: The results show that UNIS has implemented integrated strategies including doctoral study support, publication incentives, professional training, and performance-based allowances. Key supporting factors include leadership commitment, high lecturer motivation, and policy alignment with national standards. Challenges include limited research funding, insufficient international collaboration, and the absence of a comprehensive digital career monitoring system. Originality/Value: This study contributes to the literature on human resource management in higher education by providing context-specific insights into lecturer career development in a private Islamic university setting.